Pelaksanaan Pemenuhan Hak Pekerja Pada Toko Ponsel - Darma, Shabrina Rika; Lestari, Rika; Rasudin, Nurahim (PATTIMURA Legal Journal, 2024)
Introduction: The implementation of the fulfillment of workers' rights in mobile phone shops in Dumai City is often not in line with applicable regulations such as the provision of inadequate wages, workers' working hours that are not in accordance with working hour regulations and the right to leave that workers rarely get. Purposes of the Research: The purpose of this research is to find out how the fulfillment of workers' rights at cellphone stores in Dumai City, how obstacles and efforts in fulfilling workers' rights at cellphone stores in Dumai City. Methods of the Research: The type of research used is sociological legal research that wants to see the correlation between law and society, so as to reveal the effectiveness of the application of law in society. Results Originality of the Research: This research found that the only rights that have been implemented are the rights to get work breaks. Meanwhile, other rights have not been fulfilled. Constraints in the fulfillment of workers' rights are due to the absence of wage increases, working hours that exceed the time limit, unclear rights and obligations, and the lack of ability of employers to fulfill workers' rights, difficulty in obtaining work leave, absence of social security, absence of education and job training. Efforts can be made in the form of counseling and education, work scheduling so that schedules are more flexible, providing written agreements, applying appropriate wages, training and skills development, and social security.